Is Trade Good for Environment? A Unit Root Cointegration Analysis (The Pakistan Development Review, 2006)
One of the most debatable issues surrounding globalisation is the concern that trade hurts the environment, both locally and globally. Economists argue that expanding trade from domestic market to international market not only increases market share of each country but also rising competition among the nations and improve efficiency of utilising scarce resources because each country produces those goods in which she has comparative advantages. But on the other hand, environmental economists have opposed global trade and argue that the costs of spreading trade to international markets are depleting natural resources and rising pollution emissions that ultimately deteriorates environmental quality. [Copeland and Taylor (2001), Antweiler, Copeland and Taylor (2001), Chaudhuri and Pfaff (2002), Schmalensee, Stoker and Judson (1996).]